( x + x 1 ) 2 + ( x 2 + x 2 1 ) 2 + … + ( x 1 0 0 0 + x 1 0 0 0 1 ) 2
What is the value of the expression above if x 2 + x + 1 = 0 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Showing the solution suggested by Miraj Shah .
If x 2 + x + 1 = 0 ⇒ x 3 + x 2 + x = 0 ⇒ x 3 + x 2 + x + 1 = 1 ⇒ x 3 = 1 . Therefore, x is the cubic root of 1 .
⇒ x 3 = 1 = e 2 π i ⇒ x = e 3 2 π i = cos 3 2 π + i sin 3 2 π
⇒ k = 1 ∑ 1 0 0 0 ( x k + x k 1 ) 2 = k = 1 ∑ 1 0 0 0 ( e 3 2 k π i + e − 3 2 k π i ) 2 = k = 1 ∑ 1 0 0 0 ( 2 cos 3 2 k π ) 2 = k = 1 ∑ 1 0 0 0 4 cos 2 3 2 k π = 4 ( 4 1 + 4 1 + 1 + 4 1 + 4 1 + 1 + . . . + 4 1 + 1 + 4 1 ) = 4 ( 3 3 3 [ 4 1 + 4 1 + 1 ] + 4 1 ) = 3 3 3 ( 6 ) + 1 = 1 9 9 9
x 2 + x + 1 = 0 ⇒ x = ω . ( x + x 1 ) 2 + ( x 2 + x 2 1 ) 2 + . . . . . . . . . . + ( x 1 0 0 0 + x 1 0 0 0 1 ) 2 = ( 1 + 1 + 4 ) + ( 1 + 1 + 4 ) + . . . . . . . . (333 times) + 1 = 6 × 3 3 3 + 1 = 1 9 9 9 .
Easy peasy ^o^
Have you cleared iit you are in allen
Actually it is just the point of x^4=x^2+2x+1=x,
that means x^3=1, and expand the expression and one part will become (x^2+1+x)+ (x^2+1+x)+( x^2+1+x)+......+(x^2+1+x)+x^2=x^2;
another part is 1/(x^2);
the rest are just 2000;
so totally it is x^2+1/x^2+2000=1999
lol, you guys think of it with a complex way but sometimes simpleness is beauty but sometimes complexity is also beauty that is math
The above equation's roots are nothing but complex cube root of 1. This info can be used to solve the question even faster
Problem Loading...
Note Loading...
Set Loading...
L e t f ( n ) = x n + x 1 n . I f x 2 + x + 1 = 0 , w e h a v e A = f ( n ≡ 1 ( m o d 3 ) ) = − 1 , B = f ( n ≡ 2 ( m o d 3 ) ) = − 1 C = f ( n ≡ 0 ( m o d 3 ) ) = 2 . ∴ A 2 + B 2 + C 2 = 1 + 1 + 4 = 6 1 0 0 0 = 3 3 3 ∗ 3 + 1 . { ( x + x 1 ) 2 + ( x 2 + x 2 1 ) 2 + ( x 3 + x 3 1 ) 2 } + { ( x 4 + x 4 1 + ) 2 + ( x 5 + x 5 1 ) 2 + ( x 6 + x 6 1 + ) 2 } … + ( x 1 0 0 0 + x 1 0 0 0 1 ) 2 = ( A 2 + B 2 + C 2 ) + ( A 2 + B 2 + C 2 ) + . . . . . + A 2 = 3 3 3 ∗ 6 + 1 = 1 9 9 9 .